Statistical Process Control And Analytical Hierarchy Process Methods For Reducing Earth Resistance - Wahyono, Wahyono; Aulia, Nur Fatowil; Hermawan, Baktiyar Mei (Eksergi, 2023)
Security or protection systems at generators, substations, transmission, and housing and others, especially to overcome lightning disturbances and leakage currents, the earthing system must meet the required standards. For each part of the system, from transmission, substation and residential electricity utilization as well as other parts, the standard of earth resistance is not the same, for example for housing a maximum of 5 Î©, for a small generator system a maximum of 10 Î©, for a large generator a maximum of 20 Î© and so on etc. In areas where the soil type resistance is high, it is necessary to reduce the value of the earth resistance so that it reaches the Indonesian national standard. There are many ways to reduce the value of earth resistance, including lowering soil resistivity, adding electrodes to the soil, changing the type of electrode and its diameter, and so on. The aim of the research was to determine the effect of the value of earthing resistance on the depth of electrode planting and the type of soil that is affected by the water content in the soil and to apply simple statistical tools, namely Statistical Process Control (SPC) and Anlytical Hierarchy Process (AHP).The measurement method in this research uses a three-point system, namely one point for the test electrode and two points for the auxiliary electrode and the measuring instrument used to measure earth resistance is a digital earth resistance tester type digital model 4105A. This tool is designed according to international electrical commission (IEC) standards. To analyze reducing earth resistance using Statistical Process Control (SPC) and Analytical Hierarchy Process (AHP) methods. The design of this research is to answer the problems and research objectives that have been planned, namely to determine the effect of soil type on earth resistance and to analyze efforts to reduce the value of earth resistance to achieve standards with statistical process control (SPC) and analytical hierarchy process (AHP) methods. To find potential causes, it is done by calculating the analytical hierarchy process (AHP) in order to obtain a sequence of problems to be solved. If the consistency ratio value is more than 10%, then the data judgment must be corrected, but if the consistency ratio is less than or equal to 10% then the calculation results are declared correct or accepted. From the results of the AHP calculation, it is then verified by testing the earth resistance.